Pengaruh Pendidikan Anak Usia Dini (PAUD) Terhadap Kesehatan dan Status Gizi Anak - Presnanda Bijak; Syarifa Alma; Ignasisus Aryanto; Ages Tiara (Jurnal Riset Daerah, 2026)
Investing in early childhood education can bring significant educational, social, and economic benefits. Despite the presence of numerous early childhood education (PAUD) units, in 2021, Bantul Regency had the lowest Special Stunting Management Index (IKPS) compared to other regencies/cities in the Special Region of Yogyakarta Province. The suboptimal PAUD and IKPS indicators in Bantul Regency provide an opportunity for a study on the impact of PAUD on children's health and nutritional status. This study is necessary to determine whether PAUD participation rates can improve children's health and nutritional status in Bantul Regency. This study aims to analyze the effect of PAUD on stunting prevalence, used two analytical approaches: descriptive statistics and inferential statistics. The number of PAUD students statistically significantly reduced stunting prevalence across all estimation types. Meanwhile, the other two variables, the number of PAUDs and the number of PAUD teachers, did not statistically significantly reduce stunting prevalence. However, the results of simultaneous testing showed that these three PAUD variables collectively had a significant effect on stunting prevalence. There is a negative relationship between the number of PAUD students and the prevalence of stunting, which indicates that the participation of PAUD indicators plays a role in reducing stunting rates.